The White Shark (Carcharodon carcharias) in the Ancient Peruvian Ceremonial Centre of Huaca Pucllana. (9th March 2014) - Altamirano‐Sierra, A.; Vargas‐Nalvarte, P.
Abstract: New data regarding the white shark ( Carcharodon carcharias ) at the archaeological complex Huaca Pucllana (200–700 ad ) are presented on the basis of the recent discovery of teeth in ritual offering features. Previous information of this species from fossil, archaeological and modern records is reviewed. The use of the white sharks as an El Niño indicator is rejected. Past and present white shark distribution in the South East Pacific is reviewed, and the extermination of pinniped colonies as a factor in the poor modern record is discussed. Copyright © 2014 John Wiley & Sons, Ltd.